Standard form contracts and a smart contract future - Kristin B. Cornelius (Internet Policy Review, 2018)
With a budding market of widespread smart contract implementation on the horizon, there is much conversation about how to regulate this new technology. Discourse on standard form contracts (SFCs) and how they have been adopted in a digital environment is useful toward predicting how smart contracts might be interpreted. This essay provides a critical review of the discourse surrounding digitised SFCs and applies it to issues in smart contract regulation. An exploration of the literature surrounding specific instances SFCs finds that it lacks a close examination of the textual and documentary aspects of SFCs, which are particularly important in a digital environment as a shift in medium prompts a different procedural process. Instead, common perspectives are either based on outdated notions of paper versions of these contracts or on ideologies of industry and business that do not sufficiently address the needs of consumers/users in the digital age. Most importantly, noting the failure of contract law to address the inequities of SFCs in this environment can help prevent them from being codified further with smart contracts.
Keywords: 300; Standard form contracts; Terms of Service (TOS); Smart contracts